Advances in smart vehicular technology, transportation, communication and applications : proceedings of the Second International Conference on Smart Vehicular Technology, Transportation, Communication and Applications, October 25-28, 2018 Mount Emei, China, Part 2 /: proceedings of the Second International Conference on Smart Vehicular Technology, Transportation, Communication and Applications, October 25-28, 2018 Mount Emei, China, Part 2. ([2019]) - Unknown
No abstract available